The use of neem oil and chitosan during pre-harvest and in the post-harvest quality of the ‘Paluma’ guava (Revista Ciência Agronômica, 2020)
Guava is a fruit that is susceptible to attack by pests and diseases both pre- and post-harvest, making it importantto employ techniques which maintain its quality, such as the use of neem-based products and chitosan together with coldstorage. The aim of the present study was to evaluate the use of neem oil and chitosan during pre-harvest and in the post-harvestquality of the ‘Paluma’ guava. The experiment was conducted on a property in the district of Mamanguape, Paraíba. Eighteenguava trees were selected, and the following treatments were applied: a control; neem oil 0.5%; neem oil 1%; chitosan 0.5%;chitosan 1%; neem oil 0.5% + chitosan 0.5%; neem oil 0.5% + chitosan 1%; neem oil 1% + chitosan 0.5% and neem oil 1%+ chitosan 1%. When at the commercially mature stage, the fruit was harvested, packed in a harvesting crate and transportedto the Post-Harvest Physiology Laboratory (CCHSA/UFPB). The fruit was selected, stored at 24 ± 1 °C and evaluated for 10days, and then stored at 10 ± 1 °C and evaluated for 20 days, followed by physical, chemical and enzymatic analysis. Coatingwith neem oil (0.5%) + chitosan (1%) during pre-harvest proved to be effective in preserving and prolonging the quality of the‘Paluma’ guava during storage for 8 days at 24 ± 1 °C, and 16 days at 10 ± 1 °C.